Next-generation sequencing analysis of off-ladder alleles due to migration shift caused by sequence variation at D12S391 locus. (September 2016) - Fujii, Koji; Watahiki, Haruhiko; Mita, Yusuke; Iwashima, Yasuki; Miyaguchi, Hajime; Kitayama, Tetsushi; Nakahara, Hiroaki; Mizuno, Natsuko; Sekiguchi, Kazumasa
Graphical abstract: Highlights: Off-ladder (OL) alleles at D12S391 locus were analyzed with NGS using MiSeq. The relationship between the mobility data and the sequence data was examined. All OL allele 22 in nine samples had [AGAT]11 [AGAC]11 as a repeat structure. Allele 22 in the PowerPlex Fusion ladder was [AGAT]15 [AGAC]6 [AGAT]. This sequence difference was concluded to be the main cause of the OL calls. Abstract: In short tandem repeat (STR) analysis, length polymorphisms are detected by capillary electrophoresis (CE). At most STR loci, mobility shift due to sequence variation in the repeat region was thought not to affect the typing results. In our recent population studies of 1501 Japanese individuals, off-ladder calls were observed at the D12S391 locus using PowerPlex Fusion in nine samples for allele 22, one sample for allele 25, and one sample for allele 26. However, these samples were typed as ordinary alleles within the bins using GlobalFiler. In this study, next-generation sequencing analysis using MiSeq was performed for the D12S391 locus from the 11 off-ladder samples and 33 other samples, as well as the allelic ladders of PowerPlex Fusion and GlobalFiler. All off-ladder allele 22 in the nine samples had [AGAT]11 [AGAC]11 as a repeat structure, while the corresponding allele was [AGAT]15 [AGAC]6 [AGAT] for the PowerPlex Fusion ladder, and [AGAT]13 [AGAC]9 for the GlobalFiler ladder. Overall, as the number of [AGAT] in the repeat structure decreased at the D12S391 locus, the peak migrated more slowly using PowerPlex Fusion, the reverse strand of which was labeled, and it migrated more rapidly using GlobalFiler, the forward strand of which was labeled. The allelic ladders of both STR kits were reamplified with our small amplicon D12S391 primers and their mobility was also examined. In conclusion, off-ladder observations of allele 22 at the D12S391 locus using PowerPlex Fusion were mainly attributed to a relatively large difference of the repeat structure between its allelic ladder and off-ladder allele 22.